Samuel, Gad und Natan. Ein Vergleisch - Klein, Johannes (Sacra scripta, 2007)
The comparison of the three prophets points out some similarities, but also differences between them. All of them make mistakes. Samuel be- lieves he has to anoint Eliab, even though he is not the chosen one. Nathan encourages the king to build a house for the Lord, but the Lord does not need one. Maybe, even though it is not explicitly told, Gad errs as well, as he sends David to Judah. Each of the prophets announces a punishment to the king. Samuel proclaims a punishment that concerns King Saul himself – he will loose his kingdom. Nathan’s punishment concerns the king’s family – because of his affair with Batsheba David will loose four of his children. Gad’s punishment goes towards the people the king counted. Differences between the prophets appear also regarding their readiness to forgive the failure of their king. Samuel is not ready to forgive Saul, even though he is penitent. Nathan forgives David after he does penance. Gad’s forgiveness is associated with the fact, that he lets the king himself choose the punishment. His procedure is the most effective one because of his mild methods. But Gad’s effectiveness can be understood only on the background of the harshness of the methods which the other two prophets are working with.